2021
DOI: 10.1590/scielopreprints.2459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Saúde e estilo de vida de docentes considerando o nível de atividade física no lazer durante a pandemia de COVID-19

Abstract: No contexto de Pandemia da COVID-19, e necessidade de distanciamento social, professores passaram a trabalhar remotamente e tiveram mudanças nas rotinas laborais. Este trabalho buscou investigar a influência da Atividade Física no Perfil de Estilo de Vida e na Saúde Docente de professores do Ensino Fundamental - I ciclo, de um município de médio porte do Paraná no contexto do distanciamento social da Pandemia de COVID-19. Participaram 201 professores da Rede Municipal de Educação. Os instrumentos utilizados fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Regarding the practice of physical exercise during the pandemic, the fit model showed a higher prevalence of overweight among women who were not exercising, and that there was also a loss of statistical significance with regard to men. A Brazilian study carried out with teachers during the pandemic found that 60.8% were physically inactive [37]. This result was also seen in a study that evaluated the physical exercise level of Brazilians before and during the pandemic, which found a reduction in physical exercise levels for both genders, but for women, the reduction was even more relevant [38].…”
Section: Discussionmentioning
confidence: 62%
“…Regarding the practice of physical exercise during the pandemic, the fit model showed a higher prevalence of overweight among women who were not exercising, and that there was also a loss of statistical significance with regard to men. A Brazilian study carried out with teachers during the pandemic found that 60.8% were physically inactive [37]. This result was also seen in a study that evaluated the physical exercise level of Brazilians before and during the pandemic, which found a reduction in physical exercise levels for both genders, but for women, the reduction was even more relevant [38].…”
Section: Discussionmentioning
confidence: 62%
“…Acresce que, no período de ensino remoto, a vida pessoal do docente, acabou por ficar em segundo plano como podemos perceber nas falas dos participantes: D1: "A invasão do trabalho na vida privada é desgastante" D10: "Falta de infraestrutura, na minha casa não temos locais específicos para isso, o computador é dividido com outros integrantes da família" Com a necessidade imposta pela pandemia com o ensino remoto a adoção dessa modalidade de exigiu dos docentes a adequação do ambiente domiciliar e a reestruturação de seus planejamentos de ensino bem como de sua vida privada. Decorrente de ser observado indiferença e insatisfação com o seu trabalho, por vezes compartilhando componentes tecnológicos com outros membros da família; deixaram de praticar atividades físicas e por vezes abrir mão de momentos de lazer com seus familiares (Silva et al, 2021;Testa et al, 2021).…”
unclassified